2017
DOI: 10.1155/2017/5967491
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Stochastic Analysis for Lateral Vibration of Footbridge under Pedestrian Narrowband Excitation

Abstract: During the lateral vibration of footbridge, the pedestrian lateral load shows two distinct features: one is the vibration-dependency; another is the narrowband randomness caused by the variability between two subsequent walking steps. In this case, the lateral vibration of footbridge is actually a complicated, nonlinear stochastic system. In this paper, a novel nonlinear stochastic model for lateral vibration of footbridge is proposed, in which a velocity-dependent load model developed from Nakamura model is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…(5) The overall acceleration response shapes of the Eurocode loading has only one pulse, but in the actual human loading, this shape can be comprised of multi-pulse depending on the pedestrian speeds; Slow walking has two pulses, normal walking has five pulses and fast walking has three pulses. (6) The lateral accelerations of the bridge under the loading presented by the Eurocode are greater than the actual human loading. (7) The greatest amounts of acceleration responses to the actual human loadings are related to slow, normal and fast walking rates respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The overall acceleration response shapes of the Eurocode loading has only one pulse, but in the actual human loading, this shape can be comprised of multi-pulse depending on the pedestrian speeds; Slow walking has two pulses, normal walking has five pulses and fast walking has three pulses. (6) The lateral accelerations of the bridge under the loading presented by the Eurocode are greater than the actual human loading. (7) The greatest amounts of acceleration responses to the actual human loadings are related to slow, normal and fast walking rates respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also, as a result of a study, it is found out that the dynamic excitations induced by people walking together are not periodic but are narrow-band random phenomena and varies significantly not only among different people but also for a single person who cannot repeat two identical steps [5]. Another study has been proposed a nonlinear stochastic model approach for modeling lateral vibration of footbridges taking into account for narrowband randomness caused by the variability between two subsequent walking steps [6]. These studies indicate that the determination of the dynamic interaction mechanisms between the pedestrians and the bridges has been of special concern in the past few years and have been studied a lot [7].…”
Section: Introductionmentioning
confidence: 99%
“…Te results of the tests indicated that the fundamental frequency of the pedestrian bridge could be accurately refected by both the heel-drop and walking loads. However, the long duration and narrow bandwidth of the walking load generated multiple-order harmonics and high-frequency components in the frequency domain, making it challenging to distinguish the fundamental frequency of the bridge [29].…”
Section: Resultsmentioning
confidence: 99%